Evaluation of completeness of case ascertainment in Swiss cancer registration. (September 2017) - Lorez, Matthias; Bordoni, Andrea; Bouchardy, Christine; Bulliard, Jean-Luc; Camey, Bertrand; Dehler, Silvia; Frick, Harald; Konzelmann, Isabelle; Maspoli, Manuela; Mousavi, Seyed M.; Rohrmann, Sabine; Arndt, Volker
Abstract : This is the first comprehensive evaluation of completeness of case ascertainment in Swiss cancer registration. There is currently no method available that is considered to be the gold standard. Apart from simple measures such as the proportion of cases where registration was initiated by a death certificate and the proportion of diagnoses on the basis of histology or cytology/haematology, we applied two dedicated approaches: (i) the semiquantitative method of comparing the mortality to incidence rate ratio with relative survival (MI-Surv method) and (ii) the Flow method, which provides a quantitative estimate for the completeness depending on time since diagnosis. All 10 Swiss cancer registries in operation since at least 2006 and providing the required parameters were included. Simple and dedicated methods showed high completeness across all cancer registries and for most cancer types tested, with the notable exception of lymphoid leukaemia. Abstract : Supplemental Digital Content is available in the text.